Aplikasi Presensi Kerja Berbasis Android dengan Monitoring Lokasi Karyawan Secara Real-Time Menggunakan Maps - Abetnego, Dereks; Susilo, Joko (Jurnal Informatika dan Bisnis, 2024)
An effective and efficient work attendance system is key to good human resource management. In this context, the use of information technology can facilitate the process of monitoring employee locations in real-time. This research aims to implement a work attendance application system that utilizes maps services to monitor employee locations in real-time through Android devices. The application development method uses an Android-based development approach with the integration of Maps services. Users can log in and register, and then the application will automatically track their location using GPS on Android devices. The location data is then synchronized with the server in real-time.